Relative efficacy of in-organic salts as priming agent on germination, vigour, nitrate assimilation and yield in mungbean - T.N. TIWARI; DIPTI KAMAL; VARUN KUMAR; A.K. CHATURVEDI; S. RAJENDRA PRASAD (Seed Research, 2026)
A study was under taken for improving the germination, stand establishment, growth and yield of mungbean crop through the seed priming techniques. One year old seeds of three mungbean varieties (Samrat, Sulabh 2545 and SML 668) were taken and sand primed with the solutions of in- organic salts including Mg (NO₃)₂, MgSO4, and KNO3, in 30 mM concentration separately for twelve hours. A set of unprimed seeds were kept as control. Experiment was conducted in the cemented pots of 15 kg capacity during summer season in the year 2011-2012 at the research farm of Directorate of Seed Research (DSR) Mau. The results obtained revealed that priming of mungbean seeds with in-organic salts in 30 mM conc. significantly enhanced the seed germination, seedling growth, vigour, nitrate assimilatory enzymes activity, yield attributes and yield in all the varieties evaluated over unprimed control. Among the in-organic salts, the performance of Mg (NO₃)₂, was superior over others in respect of seed germination, seedling growth, vigour index 1&2 and attributes and yield whereas the activities of nitrate assimilatory enzymes viz: nitrate reductase and nitrite reductase were more influenced with KNO₃, as compared to Mg (NO₃)₂, and MgSO4, salts.